What is the role of curvature on the properties of nanomaterials for biomedical applications? - Solveyra, Estefania Gonzalez (Wiley Interdiscip Rev Nanomed Nanobiotechnol, 2015)
The use of nanomaterials for drug delivery and theranostics applications is a promising paradigm in nanomedicine, as it brings together the best features of nanotechnolgy, molecular biology and medicine. To fully exploit the synergistic potential of such interdisciplinary strategy, a comprehensive description of the interactions at the interface between nanomaterials and biological systems is not only crucial, but also mandatory. Routine strategies to engineer nanomaterial-based drugs comprise modifying their surface with biocompatible and targeting ligands, in many cases resorting to modular approaches that assume additive behavior. However, emergent behavior can be observed when combining confinement and curvature. The final properties of functionalized nanomaterials become dependent not only on the properties of their constituents but also on the geometry of the nano-bio interface, and on the local molecular environment. Modularity no longer holds, and the coupling between interactions, chemical equilibrium and molecular organization has to be directly addressed in order to design smart nanomaterials with controlled spatial functionalization envisioning optimized biomedical applications. Nanoparticle’s curvature becomes an integral part of the design strategy, enabling to control and engineer the chemical and surface properties with molecular precision. Understanding how NP size, morphology, and surface chemistry are interrelated will put us one step closer to engineering nanobiomaterials capable of mimicking biological structures and their behaviors, paving the way into applications and the possibility to elucidate the use of curvature by biological systems.